Aggregation‐Induced Emission Luminogens Sensitized Quasi‐2D Hybrid Perovskites with Unique Photoluminescence and High Stability for Fabricating White Light‐Emitting Diodes. Issue 15 (29th May 2021) - Wang, Yuanwei; Yan, Dingyuan; Wang, Lei; Wang, Dong; Tang, Ben Zhong
Abstract: In order to endow quasi‐2D organic‐inorganic hybrid metal halide perovskites (quasi‐2D‐PVK) with superior performance, an aromatic organic ligand with aggregation‐induced emission (AIE) features is rationally designed and utilized for constructing distinctive quasi‐2D‐PVK materials. This AIE‐active ligand, TTPy‐NH2, well fits into the lattices of quasi‐2D‐PVK and leaves hydrophobic tails surrounding PVK layers, making the presented TTPy‐NH2 /PVK film extraordinary in terms of both luminescence and stability. Benefiting from the prominent sensitization function and AIE tendency of TTPy‐NH2, the presented TTPy‐NH2 /PVK film exhibits a high quantum yield of 62.2%, unique blue‐red dual‐emission property of both blue and red, high stability with the remnant of more than 94% fluorescence intensity remnant after 21 days. As a result, TTPy‐NH2 /PVK film is capable of constituting high‐performance white light‐emitting diodes, with its color gamut reaching 138% of the National Television System Committee （NTSC） standard and the maximum efficiency is 105 lm W −1 at 20 mA. Evidently, a win‐win effect is achieved by the integration of AIE‐active ligands and quasi‐2D‐PVK, which are two of the most reputable solid‐state luminogens. This developed protocol thus opens up a new avenue for exploring the next generation of luminescent devices. Abstract : An aggregation‐induced emission (AIE)‐featured organic ligand TTPy‐NH2 is rationally designed and successfully utilized for sensitizing quasi‐2D‐perovskites (PVK). The fabricated TTPY‐NH2 /PVK film exhibits as high as 62.2% of quantum yield, unique dual‐emissions, and high stability, making it potential in fabricating high‐performance perovskite‐based white light‐emitting diodes. ​